The effectiveness of core stability exercises on pain in patients with low back pain: a meta-analysis - W. Wahyuni; Noofi Emma Kurnia (Physical Therapy Journal of Indonesia, 2023)
Introduction: Lower back pain (LBP) results from stress in the muscles in the lower back. The pain patients with typical back pain feel is between the lower corner of the costa and the lumbosacral caused by muscle tension in the lower back area. Based on the Results of Basic Health Research (2018), people with low back pain cannot be ascertained in Indonesia, but it is estimated to be between 7.6% to 37%. One intervention that can be given to reduce pain in patients with LBP is core stability exercise. Meta-analysis studies using PICO. P: patients with non-specific LBP. I: core stability exercise. C: non-core stability exercise. O: decrease in pain. Methods: The method of this study was a systematic review where data collection of the results of this research is carried out through searches on the PubMed and Scopus websites. Keywords used include: "low back pain" AND "non-specific low back pain" AND "core stabilization exercise" OR "core stability" OR "core exercise" AND "Randomized Controlled Trial." The selected articles are full-text articles with a randomized controlled trial method. The application is used to analyze reports in Review Manager 5.4. Results: as many as nine articles analyzed came from Korea, China, Turkey, India, Iran, the USA, and London. Studies show that patients with non-specific low back pain who received core stability exercise experienced a lower pain reduction of 0.02 than those who did not get core stability exercise, thus improving quality of life, and this effect was claimed to be statistically significant (hazard ratio (HR)= -0.02; 95% CI=-0.87 to 0.47; p<0.001). Conclusion: core stability exercise can reduce pain and have an impact on improving quality of life